Memorials in speech and writing - Jesch, Judith (Hikuin, 2005)
Rune stones are very clear evidence of the commemoration of the dead in the Viking Age. The several thousand surviving runic monuments from that period may of course have had functions other than the memorial one. They may have served to document inheritance, to rewrite history, to glorify the living rather than the dead, to support the activities of a nascent Christian church, or to demonstrate political power and allegiances.1 However, I would argue that all of these functions of such monuments, while possible, are secondary or additional. The name of the deceased is the one almost invariable feature of rune stone inscriptions, indicating that their primary function was to preserve the memory of the dead into the future.